Application of nanotechnology for remediation drill cutting soil - Zhakaw kamal Abdullah; Dalshad Azeez Darwesh (Zanco Journal of Pure and Applied Sciences, 2023)
This study was carried out for remediation of drill cutting soil from two oil field sites in Kurdistan Region of Iraq. nanotechnology was implemented. Heavy metal (Pb, Cd, Cr, Ni and petroleum hydrocarbons (C8-C24, C24-C40, TPH) were analyzed before and after remediation drill cutting soil. The experiment was designed. The results indicate that the concentration of heavy metals (Ni, Cd and Cr) was within the normal range except the concentration of Pb. The result showed that the removal rate of heavy metal by nano technic was (Pb%16, Ni %57, Cd% 48, Cr%38). And the removal rate of hydrocarbons was (TPH%57, C8-C24%62, C24-C40%41). these means the (nZVI) has effect for minimizing heavy metal and petroleum hydrocarbons in drill cutting soil.